2016
DOI: 10.11648/j.ajep.20160503.11
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Vascular and Insects Canopy Epiphytes on Palm Oil in North Sumatra, Indonesia

Abstract: This paper describes the role of the insect, which is essential for human survival, but still people are not familiar with widely even some people consider insects no meaning or viewed from the downside. Diversity of epiphytes and insects in the canopy of palm oil plantations in North Sumatra assessed by field observations at five locations, namely, Bukit Sentang, Padang Mandarsyah, Ajamu, Sijambu-jambu, and Aek Pancur. Data were analyzed using qualitative and quantitative. Based on the results obtained by ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…These species can grow well on the soil surface, indicating they are not true epiphytes. The results confirmed the findings of Suzanti et al (2016), which found that true epiphytes were uncommon in an oil palm plantation. The species of pteridophytes in the eastern region were more diverse than those in the west, as seen in Table 2.…”
Section: Epiphytes Abundancesupporting
confidence: 89%
See 2 more Smart Citations
“…These species can grow well on the soil surface, indicating they are not true epiphytes. The results confirmed the findings of Suzanti et al (2016), which found that true epiphytes were uncommon in an oil palm plantation. The species of pteridophytes in the eastern region were more diverse than those in the west, as seen in Table 2.…”
Section: Epiphytes Abundancesupporting
confidence: 89%
“…Nurdiansyah et al (2016) suggested that maintaining plant diversity and fostering weedy strips could be effective for the biological control of pests and disease. Meanwhile, vascular epiphytes may help support insect biodiversity (Suzanti et al 2016). It also increases understory vegetation, mitigates the adverse effects of forest resources, and prevents the loss of diversity (Ashton-Butt et al 2018;Nájera and Simonetti 2010).…”
Section: Ch Dd Eg Gv Nb Nbr Nc Pp Ppe Pa Ve Venmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of pest attacks in intercropping cropping patterns is lower compared to monoculture cropping patterns. This is thought to be because the intercropping pattern, apart from providing nectar from flowers needed by parasitoid and predatory insects (Saputra et al, 2023;Allifah, 2013;Kurniawati & Martono, 2015;Suswati et al, 2021;Azwana & Sihotang, 2023), also contains repellent compounds for insect pests (Nurdiansyah et al, 2016;Suzanti et al, 2016). The use of intercropping increases plant diversity in the field which can suppress pest attacks and increase the performance of natural enemies (Nirmayanti et al, 2015).…”
Section: The Influence Of Monoculture and Polyculture On The Intensit...mentioning
confidence: 99%